2017
DOI: 10.21037/atm.2017.08.27
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide: neuroendocrine communication between the pancreas, gut, and brain in regulation of blood glucose

Abstract: Background: Calcitonin gene-related peptide (CGRP), a ubiquitous neuropeptide, plays a diverse and intricate role in chronic low-grade inflammation, including conditions such as obesity, type 2 diabetes, and diabetes of the exocrine pancreas. Diabetes of exocrine pancreas is characterised by chronic hyperglycemia and is associated with persistent low-grade inflammation and altered secretion of certain pancreatic and gut hormones. While CGRP may regulate glucose homeostasis and the secretion of pancreatic and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…These population-based data are in line with the recent studies by the COMSOS group into early pathogenetic events in PPDM that showed that individuals with PPDM are characterized by hyperinsulinemia, decreased insulin sensitivity, lipolysis of adipose tissue, and gut dysfunction (among other features) (36)(37)(38)(39)(40)(41)(42)(43)(44), which can (at least in part) be reverted by metformin. In addition, a 2018 study showed that the antidiabetic effect of metformin in living cells is linked to iron metabolism (45), and two 2018 clinical studies by the COSMOS group independently established the connection between iron metabolism and PPDM (46,47).…”
Section: Discussionsupporting
confidence: 85%
“…These population-based data are in line with the recent studies by the COMSOS group into early pathogenetic events in PPDM that showed that individuals with PPDM are characterized by hyperinsulinemia, decreased insulin sensitivity, lipolysis of adipose tissue, and gut dysfunction (among other features) (36)(37)(38)(39)(40)(41)(42)(43)(44), which can (at least in part) be reverted by metformin. In addition, a 2018 study showed that the antidiabetic effect of metformin in living cells is linked to iron metabolism (45), and two 2018 clinical studies by the COSMOS group independently established the connection between iron metabolism and PPDM (46,47).…”
Section: Discussionsupporting
confidence: 85%
“…Taken together, these data suggest that, contrary to common belief, mechanical destruction of the islets of Langerhans as a result of pancreatic necrosis (with or without surgery) is not the only cause of PPDM-A. The pathogenesis of PPDM-A is being actively investigated, with the key mechanisms identified thus far being persistent low-grade inflammation 32–34 , dysfunction of the pancreas-gut-brain axis 35–37 , lipolysis of adipose tissue 38–40 and insulin resistance 41–43 .…”
Section: Sequelae Of Pancreatitismentioning
confidence: 90%
“…For example, a 2014 study showed that α-melanocyte stimulating hormone triggers secretion of GLP-1 and peptide YY from the L cells [30]. Another study demonstrated that gastrin-releasing peptide is significantly associated with peptide YY [31] whereas calcitonin gene-related peptide and vasoactive intestinal peptide are significantly associated with oxyntomodulin [32,33]. Investigation of circulating levels of oxyntomodulin in individuals with NODAP vs. type 2 diabetes is now warranted to determine if decreased oxyntomodulin levels are a characteristic feature of NODAP.…”
Section: Associations Between Gut Hormones and Indices Of Insulin Secmentioning
confidence: 99%